MYRIAD PROBLEMS OF TEACHERS AND ITS IMPLICATIONS ON QUALITY EDUCATION IN NIGERIA - Garba, Sheriff (PEOPLE: International Journal of Social Sciences, 2015)
In Nigeria, the teaching force is demoralized with little motivation. Teachers previously benefiting from considerable public respects and reasonable financial rewards, their status is today in exponential decay. The crises in the teaching profession are threatening the ability of Nigeria to reach internationally agreed targets to expand and improve education. To this regard, the study focuses on the situation of teachers in Nigeria today, the myriad problems they are facing and the detrimental effect these problems are having on children’s ability to have quality education. The paper argues that the survival of Nigeria as a viable society will depend on the health of her educational institutions, more especially, on how well the teachers that are the backbone of quality education are treated. In an attempt to identify and find solution to the problems, the paper used participatory advocacy research methodology to explore teachers’ views of their profession. What actually motivates teachers? What affects their morale? In addition, what will help them perform well? The problems and prospects gathered from the voices of teachers and educationists came out with holistic recommendations on how teachers’ motivation and morale could be improved, in order to have a virile and quality education in Nigeria. It is expected that the outcomes of the study may benefit the overall population of Nigerians, with special reference to education policy formulators and implementers. It serves as a media through which teachers problems and voices will be spread and be heard. It is also hope that an efficient education policy that will address the myriad problems of teachers will have a positive impact on the overall development of socio-economic and political aspects of the entire country.